Yield and anatomical characters in Hevea: A path coefficient analysis and characterisation of clones - Premakumari D; Marattukalam J G; Panikkar A O N; Sethuraj M R (Indian Journal of Natural Rubber Research, 1996)
Ten clones of Hevea brasiliensis were characterised for early yield, girth and bark anatomical traits. Genotypic correlations and direct/indirect effects of girth and structural traits with yield were estimated. Laticifer area index at the year of opening was the most reliable parameter for early prediction of yield which showed the highest positive correlation (r=0.691;P<0.01) and highest positive direct effect (1.832) on yield over the subsequent three years. The intensity of laticifer anastomosing and ray width also directly contributed to yield and were observed to be independent characters. The number of latex vessel rows showed significant positive correlation with yield (r=0.589;P<0.01) but its direct effect was negative. Correlation of girth, latex vessel density and latex vessel diameter with yield were not significant. These traits and the number of latex vessel rows contributed to yeild via laticifer area index.
Keywords: Bark anatomy; Bark anatomy; Hevea; Hevea; Latex vessels; Latex vessels; Yield; Yield